Developing a competence framework for psychological interventions in a multidisciplinary paediatric context - Anthony David Roth; Janie Donnan (BMJ Publishing Group, 2019)
This paper describes the development and content of a competence framework for psychological interventions, intended to apply to healthcare workers of all disciplines working in a paediatric context. To achieve this, a review of the literature was used to indicate where current interventions had evidence for efficacy; this scoping exercise was complemented by an expert reference group (ERG) whose role was to offer professional advice on areas where the evidence base is not strong but where the field commonly employs interventions. Iterative peer review of the emerging framework was undertaken both by the ERG and external peer reviewers selected for their expertise in the field. The characteristics of the completed framework are presented, along a discussion of the uses to which it can be put. The framework is best seen as a practitioner support tool, providing a basis for training and practice in paediatric contexts.